The Pingding segment of the Altyn Tagh Fault (91°E) : holocene slip-rate determination from cosmogenic radionuclide dating of offset fluvial terraces - Lasserre, C. (2013)
Morphochronologic slip-rates on the Altyn Tagh Fault (ATF) along the southern front of the Pingding Shan at ∼90.5°E are determined by cosmogenic radionuclide (CRN) dating of seven offset terraces at two sites. The terraces are defined based upon morphology, elevation and dating, together with fieldwork and high-resolution satellite analysis. The majority of the CRN model ages fall within narrow ranges (<2 ka) on the four main terraces (T1, T2, T3 and T3′), and allow a detailed terrace chronology. Bounds on the terrace ages and offsets of 5 independent terraces yield consistent slip-rate estimates. The long-term slip-rate of 13.9 ± 1.1 mm/yr is defined at the 95% confidence level, as the joint rate probability distribution of the rate derived from each independent terrace. It falls within the bounds of all the rates defined on the central Altyn Tagh Fault between the Cherchen He (86.4°E) and Akato Tagh (∼88°E) sites. This rate is ∼10 mm/yr less than the upper rate determined near Tura at ∼87°E, in keeping with the inference of an eastward decreasing rate due to progressive loss of slip to thrusts branching off the fault southwards but it is greater than the 9 ± 4 mm/yr rate determined at ∼90°E by GPS surveys and other geodetic short-term rates defined elsewhere along the ATF. Whether such disparate rates will ultimately be reconciled by a better understanding of fault mechanics, resolved transient deformations during the seismic cycle or by more accurate measurements made with either approach remains an important issue.